Shell effects in Duflo-Zuker inspired mass formulas: A status report - Barbero, César Alberto (2014)
Attempts to simplify and improve the Duflo-Zuker (DZ) mass formula are reported. The "master term", which relates the volume and surface terms in the Liquid Drop Model with the microscopic monopole interaction, is modified to incorporate directly the observed shell effects in four different ways. They are, however, less successful than the macroscopic sector of the DZ model, and than those inspired in the F-spin symmetry.